MENINGKATKAN HASIL BELAJAR MENGGUNAKAN STRATEGI PEMBELAJARAN PROBLEM BASED LEARNING - Melania Dela Sarkol; Jantje Ngangi; Anatje Anatje (SOSCIED, 2023)
Based on observations made at SMAN 2 TONDANO, the biology learning process in the classroom still has several problems that cause less than optimal learning. Students just listen to what the teacher says. One of the learning models that can increase the activeness of students is the Problem Based Learning (PBL) learning model. The purpose of this study was to improve student learning outcomes through the application of the Problem-based learning (PBL) learning model to the biology learning outcomes of class XI students on the material of the human motion system at SMA Negeri 2 Tondano. The method used in this research process is classroom action research (PTK) with 2 cycles. This research was conducted at SMA Negeri 2 Tondano, Minahasa Regency with the subject of this research were students of class XI IPA SMA N 2 Tondano, with a total of 20 students. From the learning actions in cycle I, the results of student learning completeness only reached 59%. While in cycle II, it increased to 86%. Thus, it can be concluded that the application of the Problem Based Learning learning model can improve Biology learning outcomes with the subject matter "Motion System in Humans" in class XI IPA SMA N 2 Tondano